Philomena - Frears, Stephen; Dench, Judi, 1934-; Coogan, Steve; Fairley, Michelle; Desplat, Alexandre; Sixsmith, Martin (Beverly Hills, CA : Anchor Bay Entertainment, 2014)
A woman searches for her lost son, who was taken away from her many years ago after she was forced to live in a convent after she became pregnant.
Originally released as a motion picture in 2013.
Based on the book "The lost child of Philomena Lee" by Martin Sixsmith.
Wide screen 1.77:1.
Camera, Robbie Ryan ; production designer, Alan MacDonald ; editor, Valerio Bonelli ; music, Alexandre Desplat.
Judi Dench, Steve Coogan, Michelle Fairley, Barbara Jefford, Anna Maxwell Martin.
MPAA rating: PG-13.
Keywords: Sixsmith, Martin -- Film adaptations; Mothers and sons -- Drama; Unmarried mothers -- Drama; Illegitimate children -- Drama; Fiction films; Based on the book; Feature films